Results of Ventriculoperitoneal Shunt Surgery among Patients with Normal Pressure Hydrocephalus - Farrukh Zulfiqar, Muhammad Asim Khan Rehmani, Zaheen Shibli, Qazi Muhammad Zeeshan, Ramesh Kumar, Muhammad Faaiq Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: An evaluation of the outcomes and risk factors for idiopathic normal-pressure hydrocephalus patients treated with Ventriculoperitoneal (VP) shunt Methods: The retrospective analysis of 72 patients who were hospitalized to our institution and diagnosed with suspected idiopathic normal-pressure hydrocephalus (iNPH) were included. All of the patients in this research had VP-shunt surgery with a programmable valve, and their results were evaluated six months and two years following surgery, respectively, by means of the modified Rankin scale (mRS) and the Krauss index. Both multivariate and univariate regression analysis were used to recognize the factors of prognosis. Results: 54 men and 18 women were among the 72 patients with probable iNPH, with an average age of 70.4 ± 7.2 years. Symptoms lasted an average of 22.5±17.9 months. In the majority of patients, gait imbalance was the most prevalent presenting symptom. 90.3 percent of patients reported gait imbalance, urinary incontinence in 66.6%, and 52.7 percent had cognitive impairment. 126.8± 37.2 mm H2O was the average lumbar opening pressure. During shunt implantation, the initial pressure of the valve was determined depending on the surgeon’s preference and lumbar opening pressure. The average starting valve pressure was 94.80± 21.88 mm H2O. Six months following surgery, 58 percent of the 72 patients improved their mRS scores, with 60 percent improving one step and 15.7 percent improving two steps. At 6 months after surgery, the proportion of subjects who were able to live independently (mRS score 1–2) augmented from 55.5 to 86.1 percent. The Krauss index after two years was 0.55 ± 0.29; 21 (65.2%) subjects had an index >0.5 and 68.1% of 38 patients were living independently (mRS 0–2). Particularly, at 6-month and 2-year results later to VP-shunt surgery did not vary substantially (p > 0.05). Conclusion: Patients with iNPH who underwent VP-shunts reported that their surgical therapy was well tolerated. The majority of patients reported a reduction in the severity of their preoperative symptoms. Patients with iNPH should be evaluated for the presence of several parallel co-morbidities, which must be regarded as unfavourable factor of prognosis.